Friendships in preschool children with autism spectrum disorder: What holds them back, child characteristics or teacher behavior?. (January 2016) - Chang, Ya-Chih; Shih, Wendy; Kasari, Connie
Children begin to show preferences for specific playmates as early as the first 2 years of life. Children with autism spectrum disorder have difficulty making friends, even in elementary and middle school. However, very little is known about earlier friendships in children with autism such as preschool friendships. This study examined friendships in preschool children with autism and explored how joint attention contributes to these friendships in mainstream settings. A secondary aim was to determine the extent to which teachers used strategies to facilitate friendship development. The participants were 31 mainstreamed preschool children (ages 2–5 years) with autism spectrum disorder. School observations were conducted individually to capture participants' interactions with peers and adults during free play. The results indicated that 20% of the participants had friendships at school. Children with friends were more likely than children without friends to be jointly engaged with their peers during free play, and they used higher joint attention skills. Teachers used few friendship facilitating strategies, and more often used behavioral management strategies within the classrooms. Future studies may want to examine the effects of early interventions and/or teacher training on the development of friendships in preschool children with autism spectrum disorder within the school setting.